Blowout - Duhamel, Denise (Pitt poetry series., 2013)
The poet asks the same question that Frankie Lyman & the Teenagers asked back in 1954: Why do fools fall in love? The poet readily admits that she is a love-struck fool, but also embraces the "crazy wisdom" of the Fool of the Tarot deck and the fool as entertainer or jester. From a kindergarten crush to a failed marriage and beyond, these poems explore the nature of romantic love and limitations. The poet also examines love through music, film, and history - including Michelle and Barack Obama's inauguration and Cleopatra's ancient sex toy. The poet chronicles the perilous cruelties of love gone awry, but also reminds us of the compassion and transcendence in the aftermath. In this book, she asserts that 'love poems are the most difficult poems to write / because each poem contains its opposite its loss / and that no matter how fierce the love of a couple / one of them will leave the other / if not through betrayal / then through death.' Despite this, she embraces the poetry of love.--adapted from publisher's description.